Comparative Yield Response and Sugar Contents of Four Sweet Corn Varieties Under Different Shallow Subsurface Drip Irrigation Treatments - Moussa Theodore Yatta; Allen Thompson; Tim Reinbott; Anthony Lupo; Kerry Clark; Noel Aloysius (Irrigation and Drainage, 2026)
This study evaluated the impacts of three water application treatments—potential evapotranspiration (PET), crop‐specific evapotranspiration (Crop‐ET) and rainfed (no irrigation)—on the growth, yield and quality of sweet corn ( Zea mays ) via shallow subsurface drip irrigation. During the 2022 growing season, the study utilised a randomised split‐plot design with four sweet corn hybrids (Ambrosia F1 SE, Temptress F1 SG, Honey and Cream F1 SU, and Peaches and Cream F1 HSE) and three irrigation replicates. PET‐based irrigation calculated using the modified Penman–Monteith equation often results in overirrigation, especially during early growth stages. In contrast, Crop‐ET, calculated with crop coefficients, more effectively matches crop water needs, improving irrigation efficiency and conserving resources. Compared with Crop‐ET plots, rainfed plots were most vulnerable to dry spells and, on average, produced ~25–35% fewer ears ha −1 and ~30–45% lower total ear mass. Peaches and Cream F1 HSE demonstrated strong resilience and biomass production under all treatments, whereas Ambrosia F1 SE presented high sugar contents but greater sensitivity to water stress. Soil texture and moisture retention significantly influenced irrigation effectiveness and water availability. These findings emphasise the importance of tailored irrigation strategies based on crop‐specific water requirements and soil properties, alongside drought‐tolerant hybrid selection, to maximise yield and improve quality in water‐limited regions. Future research should address multi‐season variability and include deeper soil moisture dynamics.

In situ evaluation of an active-passive sampling (APS) technique for monitoring psychoactive compounds in effluent wastewater - Allen Jun Anies; Maria Laimou-Geraniou; Maarten Quireyns; Tim Boogaerts; Cara Byns; Taja Verovšek; David Heath; Ester Heath; Alexander L.N. van Nuijs; Adrian Covaci; Ronny Blust; Raewyn M. Town (Environmental Pollution, 2026)

Sorption of psychoactive compounds on passive sampling sorbents in the presence of wastewater suspended particulate matter - Allen Jun Anies; Jiaguo He; Senne Lefever; Tim Boogaerts; Adrian Covaci; Ronny Blust; Raewyn M. Town (Environmental Pollution, 2025)

The Utility of Fish Population Monitoring and Forecast Trigger Development for Designing Adaptive Aquatic Monitoring Plans for Large Industrial Developments - Carolyn JM Brown; Tim J. Arciszewski; R. Allen Curry; D. Scott Smith; Kelly R. Munkittrick (Environmental Management, 2025)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Workflow to facilitate the detection of new psychoactive substances and drugs of abuse in influent urban wastewater - Richard Bade; Denice van Herwerden; Nikolaos Rousis; Sangeet Adhikari; Darren Allen; Christine Baduel; Lubertus Bijlsma; Tim Boogaerts; Dan Burgard; Andrew Chappell; Erin M. Driver; Fernando Fabriz Sodre; et al. (Journal of Hazardous Materials, 2024)

Towards reusable building blocks for agent-based modelling and theory development - Uta Berger; Andrew Bell; C. Michael Barton; Emile Chappin; Gunnar Dreßler; Tatiana Filatova; Thibault Fronville; Allen Lee; Emiel van Loon; Iris Lorscheid; Matthias Meyer; Birgit Müller; et al. (Environmental Modelling & Software, 2024)

Longitudinal aortic strain, ventriculo-arterial coupling and fatty acid oxidation: novel insights into human cardiovascular aging - Hongzhou Zhang; Shuang Leng; Fei Gao; Jean-Paul Kovalik; Ru-San Tan; Hai Ning Wee; Kee Voon Chua; Jianhong Ching; Xiaodan Zhao; John Allen; Qinghua Wu; Tim Leiner; et al. (GeroScience, 2024)

Casino-based cash transfers and fertility among the Eastern Band of Cherokee Indians in North Carolina: A time-series analysis - Parvati Singh; Alison Gemmill; Tim-Allen Bruckner (Economics & Human Biology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Increased expression of plasminogen activator inhibitor-1 (PAI-1) is associated with depression and depressive phenotype in C57Bl/6J mice - René A. Girard; Prashant S. Chauhan; Torry A. Tucker; Tim Allen; Jaswinder Kaur; Ann Jeffers; Kathleen Koenig; Galina Florova; Andrey A. Komissarov; Tatiana A. Gaidenko; Mignote B. Chamiso; James Fowler; et al. (Experimental Brain Research, 2019)

Forced summer stationary waves: the opposing effects of direct radiative forcing and sea surface warming - Hugh S. Baker; Tim Woollings; Cheikh Mbengue; Myles R. Allen; Christopher H. O’Reilly; Hideo Shiogama; Sarah Sparrow (Climate Dynamics, 2019)

Uncertainty in geomorphological responses to climate change - Stephan Harrison; Tim Mighall; David A. Stainforth; Philip Allen; Mark Macklin; Edward Anderson; Jasper Knight; Dmitri Mauquoy; David Passmore; Brice Rea; Matteo Spagnolo; Sarah Shannon (Climatic Change, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Assessing mid-latitude dynamics in extreme event attribution systems - Daniel Mitchell; Paolo Davini; Ben Harvey; Neil Massey; Karsten Haustein; Tim Woollings; Richard Jones; Fredi Otto; Benoit Guillod; Sarah Sparrow; David Wallom; Myles Allen (Climate Dynamics, 2017)

Best practice BioBanking of human heart tissue - Sean Lal; Amy Li; David Allen; Paul D. Allen; Paul Bannon; Tim Cartmill; Roger Cooke; Alan Farnsworth; Anne Keogh; Cristobal dos Remedios (Biophysical Reviews, 2015)

Characterisation of 9 polymorphic microsatellite markers for the Critically Endangered lemur leaf frog Agalychnis lemur - Alex Petchey; Andrew Gray; Claes Andrén; Tim Skelton; Brian Kubicki; Calvin Allen; Robert Jehle (Conservation Genetics Resources, 2014)

Erratum: A decadal decline in relative abundance and a shift in microphytoplankton composition at a long‐term coastal station off southeast Australia - Penelope A. Ajani; Andrew P. Allen; Tim Ingleton; Leanne Armand (Limnology and Oceanography, 2014)

D r . H al M arkowitz 1934–2012 - Sarah Allen; Frances Gulland; Tim Markowitz; Jonathan Stern; Isidore Szczepaniak; Greg Timmel; Bernd Würsig (Marine Mammal Science, 2014)

A decadal decline in relative abundance and a shift in microphytoplankton composition at a long‐term coastal station off southeast Australia - Penelope A. Ajani; Andrew P. Allen; Tim Ingleton; Leanne Armand (Limnology and Oceanography, 2014)
In this study, we examined 11 yr (1998–2009) of water samples collected from Port Hacking coastal monitoring station 8 km offshore from Sydney, Australia, to assess changes in the microphytoplankton in relation to climate‐related trends in environmental variables. A total of 152 taxa (85 genera) were identified, with the small diatom Thalassiosira cf. partheneia and the tropical cyanobacterium Trichodesmium erythraeum being the dominant species over the past decade. Taxon richness showed a distinct seasonal pattern, peaking in the austral winter. Ordination analyses revealed significant seasonal and interannual trends in species composition, including a decadal decline in dinoflagellates relative to diatoms toward the present. This decadal shift in taxonomic composition was, in turn, significantly associated with declines in water temperatures over this time period. Total abundance varied by 12 orders of magnitude (8.5 × 10 −8 to 7.4 × 10 4 cells L −1 ), with values separable into bloom and nonbloom regimes at an abundance threshold of 7.1 × 10 −5 cells L −1 . Significant temporal declines in abundance were observed during both bloom and nonbloom regimes. Blooms occurred most consistently in March, September, and December.

Isolation of Functional Human Endothelial Cells from Small Volumes of Umbilical Cord Blood - Sa Do Kang; Tim A. Carlon; Alexandra E. Jantzen; Fu-Hsiung Lin; Melissa M. Ley; Jason D. Allen; Thomas V. Stabler; N. Rebecca Haley; George A. Truskey; Hardean E. Achneck (Annals of Biomedical Engineering, 2013)

The Feasibility of Producing Adequate Feedstock for Year-Round Cellulosic Ethanol Production in an Intensive Agricultural Fuelshed - Daniel R. Uden; Rob B. Mitchell; Craig R. Allen; Qingfeng Guan; Tim D. McCoy (BioEnergy Research, 2013)

An assessment of air pollution and its attributable mortality in Ulaanbaatar, Mongolia - Ryan W. Allen; Enkhjargal Gombojav; Baldorj Barkhasragchaa; Tsogtbaatar Byambaa; Oyuntogos Lkhasuren; Ofer Amram; Tim K. Takaro; Craig R. Janes (Air Quality, Atmosphere & Health, 2013)

Palaeodiet at Eton College Rowing Course, Buckinghamshire: isotopic changes in human diet in the Neolithic, Bronze Age, Iron Age and Roman periods throughout the British Isles - Rhiannon E. Stevens; Emma Lightfoot; Tim Allen; Robert E. M. Hedges (Archaeological and Anthropological Sciences, 2012)

Consumption of meat and fish and risk of lung cancer: results from the European Prospective Investigation into Cancer and Nutrition - Jakob Linseisen; Sabine Rohrmann; Bas Bueno-de-Mesquita; Frederike L. Büchner; Hendriek C. Boshuizen; Antonio Agudo; Inger Torhild Gram; Christina C. Dahm; Kim Overvad; Rikke Egeberg; Anne Tjønneland; Heiner Boeing; et al. (Cancer Causes & Control, 2011)

Integrating Environmental and Socio-Economic Indicators of a Linked Catchment–Coastal System Using Variable Environmental Intensity - John R. Dymond; Tim J. A. Davie; Andrew D. Fenemor; Jagath C. Ekanayake; Ben R. Knight; Anthony O. Cole; Oscar Montes de Oca Munguia; Will J. Allen; Roger G. Young; Les R. Basher; Marc Dresser; Chris J. Batstone (Environmental Management, 2010)

Balancing bias and precision in capture‐recapture estimates of abundance - Nancy A. Friday; Tim D. Smith; Peter T. Stevick; Judy Allen; Tom Fernald (Marine Mammal Science, 2008)
Capture‐recapture estimates of abundance using photographic identification data are sensitive to the quality of photographs used and distinctiveness of individuals in the population. Here analyses are presented for examining the effects of photographic quality and individual animal distinctiveness scores and for objectively selecting a subset of data to use for capture‐recapture analyses using humpback whale ( Megaptera novaeangliae ) data from a 2‐year study in the North Atlantic. Photographs were evaluated for their level of quality and whales for their level of individual distinctiveness. Photographic quality scores had a 0.21 probability of changing by a single‐quality level, and there were no changes by two or more levels. Individual distinctiveness scores were not independent of photographic quality scores. Estimates of abundance decreased as poor‐quality photographs were removed. An appropriate balance between precision and bias in abundance estimates was achieved by removing the lowest‐quality photographs and those of incompletely photographed flukes given our assumptions about the true population abundance. A simulation of the selection process implied that, if the estimates are negatively biased by heterogeneity, the increase in bias produced by decreasing the sample size is not more than 2%. Capture frequencies were independent of individual distinctiveness scores.

Anthropometric factors and risk of endometrial cancer: the European prospective investigation into cancer and nutrition - Christine Friedenreich; Anne Cust; Petra H. Lahmann; Karen Steindorf; Marie-Christine Boutron-Ruault; Françoise Clavel-Chapelon; Sylvie Mesrine; Jakob Linseisen; Sabine Rohrmann; Heiner Boeing; Tobias Pischon; Anne Tjønneland; et al. (Cancer Causes & Control, 2007)

Intake of fruits and vegetables and risk of cancer of the upper aero-digestive tract: the prospective EPIC-study - Heiner Boeing; Thomas Dietrich; Kurt Hoffmann; Tobias Pischon; Pietro Ferrari; Petra H. Lahmann; Marie Christine Boutron-Ruault; Francoise Clavel-Chapelon; Naomi Allen; Tim Key; Guri Skeie; Eiliv Lund; et al. (Cancer Causes & Control, 2006)

A scaling approach for quantifying the net CO 2 flux of the Kuparuk River Basin, Alaska - Walter C. Oechel; George L. Vourlitis; Joseph Verfaillie; Tim Crawford; Steve Brooks; Edward Dumas; Allen Hope; Douglas Stow; Bill Boynton; Viktor Nosov; Rommel Zulueta (Global Change Biology, 2000)
Summary Net CO 2 flux measurements conducted during the summer and winter of 1994–96 were scaled in space and time to provide estimates of net CO 2 exchange during the 1995–96 (9 May 1995–8 May 1996) annual cycle for the Kuparuk River Basin, a 9200 km 2 watershed located in NE Alaska. Net CO 2 flux was measured using dynamic chambers and eddy covariance in moist‐acidic, nonacidic, wet‐sedge, and shrub tundra, which comprise 95% of the terrestrial landscape of the Kuparuk Basin. CO 2 flux data were used as input to multivariate models that calculated instantaneous and daily rates of gross primary production (GPP) and whole‐ecosystem respiration ( R ) as a function of meteorology and ecosystem development. Net CO 2 flux was scaled up to the Kuparuk Basin using a geographical information system (GIS) consisting of a vegetation map, digital terrain map, dynamic temperature and radiation fields, and the models of GPP and R . Basin‐wide estimates of net CO 2 exchange for the summer growing season (9 May−5 September 1995) indicate that nonacidic tundra was a net sink of −31.7 ± 21.3 GgC (1 Gg = 10 9 g), while shrub tundra lost 32.5 ± 6.3 GgC to the atmosphere (negative values denote net ecosystem CO 2 uptake). Acidic and wet sedge tundra were in balance, and when integrated for the entire Kuparuk River Basin (including aquatic surfaces), whole basin summer net CO 2 exchange was estimated to be in balance (−0.9 ± 50.3 GgC). Autumn to winter (6 September 1995–8 May 1996) estimates of net CO 2 flux indicate that acidic, nonacidic, and shrub tundra landforms were all large sources of CO 2 to the atmosphere (75.5 ± 8.3, 96.4 ± 11.4, and 43.3 ± 4.7 GgC for acidic, nonacidic, and shrub tundra, respectively). CO 2 loss from wet sedge surfaces was not substantially different from zero, but the large losses from the other terrestrial landforms resulted in a whole basin net CO 2 loss of 217.2 ± 24.1 GgC during the 1995–96 cold season. When integrated for the 1995–96 annual cycle, acidic (66.4 + 25.25 GgC), nonacidic (64.7 ± 29.2 GgC), and shrub tundra (75.8 ± 8.4 GgC) were substantial net sources of CO 2 to the atmosphere, while wet sedge tundra was in balance (0.4 + 0.8 GgC). The Kuparuk River Basin as a whole was estimated to be a net CO 2 source of 218.1 ± 60.6 GgC over the 1995–96 annual cycle. Compared to direct measurements of regional net CO 2 flux obtained from aircraft‐based eddy covariance, the scaling procedure provided realistic estimates of CO 2 exchange during the summer growing season. Although winter estimates could not be assessed directly using aircraft measurements of net CO 2 exchange, the estimates reported here are comparable to measured values reported in the literature. Thus, we have high confidence in the summer estimates of net CO 2 exchange and reasonable confidence in the winter net CO 2 flux estimates for terrestrial landforms of the Kuparuk river basin. Although there is larger uncertainty in the aquatic estimates, the small surface area of aquatic surfaces in the Kuparuk river basin (≈ 5%) presumably reduces the potential for this uncertainty to result in large errors in basin‐wide CO 2 flux estimates.

MEASUREMENT OF PHOTOGRAPHIC QUALITY AND INDIVIDUAL DISTINCTIVENESS FOR THE PHOTOGRAPHIC IDENTIFICATION OF HUMPBACK WHALES, MEGAPTERA NOVAEANGLIAE - Nancy Friday; Tim D. Smith; Peter T. Stevick; Judy Allen (Marine Mammal Science, 2000)
A bstract Accurate identification of humpback whales from photographic identification data depends on the quality of the photographs and the distinctiveness of the flukes. Criteria for evaluating photographic quality and individual distinctiveness were developed involving judgments about overall quality or distinctiveness and about specific aspects of each. These criteria were tested for the level of agreement among judges. The distinctiveness scheme was tested for the independence of distinctiveness judgments and photographic quality. Our results show that judges could agree when evaluating specific and overall aspects of photographic quality and individual distinctiveness. The level of agreement varied for different pairs of judges, and less adept judges were identified. Ability to agree on evaluations of photographic quality was independent of the experience of the judges. Overall photographic quality and overall distinctiveness were successfully predicted from more specific variables, but the agreement between judges for these was not significantly greater than the agreement for the overall measures judged directly. There was no correlation between individual distinctiveness and photographic quality for four of the five judges, but the power of this rest may be low. Analyses of photographic identification data frequently require evaluations of photographic quality and individual distinctiveness. To obtain reliable results from such analyses, evaluation schemes and judges should be tested to ensure reliable and consistent evaluations.